Pleistocene vertebrate trace fossils of Robberg Nature Reserve - Helm, Charles W.; Cawthra, Hayley C.; Hattingh, Rudolph; Hattingh, Sinèad; McCrea, Richard T.; Thesen, Guy H. H. (Evolutionary Studies Institute, 2019)
More than 140 Late Pleistocene trace fossil sites have been identified in aeolianites and lithified foreshore deposits along a 350 kilometre stretch of the Cape south coast in South Africa. Robberg Nature Reserve lies within this area and contains a zone of concentration of such tracksites, which complement the Pleistocene vertebrate body fossil record and assist in shedding light on the palaeoenvironment and palaeoecology of the Palaeo-Agulhas Plain. Ichnofossil sites unique to or of special significance within Robberg Nature Reserve include a substantial palaeosurface exposure that allows an estimate of track density, the best-preserved rhinoceros trackway identified to date, very well preserved artiodactyl tracks in the formof natural casts, small equid tracks, large elephant transmitted tracks, and well preserved sub-surface golden mole burrows with a burrow chamber. Aeolianite layers at Robberg have recently been dated to Marine Isotope Stage (MIS) 3. Samples that we have obtained for dating from the main palaeosurface underlie these dated layers and are anticipated to contribute to the understanding of the Pleistocene geology of the Robberg Peninsula. The protected status of the area lends itself to conservation, replication, interpretation and education initiatives.
Keywords: Late Pleistocene; trackways; aeolianites; foreshore deposits